Back to Java: The discourse of Lombok art in Salman Faris’s Kenari Mentaram - Dharma Satrya HD; Baiq Rismarini Nursaly (EduLite: Journal of English Education, Literature and Culture, 2021)
This article is triggered by the emergence of ethnicity aspects in Indonesian literature. The importance of ethnicity in Indonesian literature is because Indonesian literature is assumed to be plural, not singular. That is, the reality of Indonesia in Indonesian literature is not limited to one ethnicity, but various ethnicities. In the perspective of modern Indonesian literature, Indonesian novels are synonymous with Malay, Jakarta, Java and several other cities that have contributed to the development of Indonesian literature. In the perspective of ethnic Indonesian literature, Indonesian novels are identical with ethnicities whose existence is ignored in modern Indonesian literature. In this context, ethnic Indonesian literature is important to explore. This article explores the interesting representation of Lombok in Ethnic Indonesian literature. Lombok serves an ethnic that needs to be analyzed in Indonesian literature, because Lombok is assumed to be part of Java (Marrison, 1999; Meij 2011) and Lombok is hegemonyed in Java (Satrya, 2018). The problem is whether Indonesian literature still represents Lombok as shown by Marrison, Meij, and Satrya in the study of philology and literature. The Indonesian novel of Lombok delineating the issue of Java in interpreting Lombok is the novel Kenari Mentaram (2013) by Salman Faris. This article applies Stuart Hall’s representation theory and model. Based on that theory, the novel Kenari Mentaram is assumed to be a production of meaning regarding Lombok. The analytical method uses the semiotic analysis method and the Stuart Hall discourse model. Lombok is interpreted in the novel Kenari Mentaram in the context of internationalization. In this context, Lombok's art is the only commodity that can be sold. The art of Lombok represented is the art of Lombok which is capable of competing internationally by taking a model from Java. Thus, the internationalization of Lombok can only be done by taking the Javanese Model. In the  internationalization context, the discourse of Lombok art discussed is the multicultural art of Lombok. The Kenari Mentaram novel delineates as part of the discourse of the nationalization of Lombok in the context of Indonesian literature and the internationalization of Lombok in the context of tourism.